Iconography as biography : a study of the Middle Kingdom Egyptian tombs at Beni Hasan, el-Bersha and Meir (c.2040-1840 B.C.) - Baines, Alice Victoria (Stellenbosch : Stellenbosch University, 2012)
Dissertation (DPhil)--Stellenbosch University, 2021.